Öğrencilerin İş Birliğine Dayalı Problem Çözme Yönteminin Uygulandığı Öğrenme Ortamına İlişkin Görüşleri. - ÜNAL, Üyesi Erhan; ÇAKIR, Hasan (Afyon Kocatepe University Journal of Social Sciences / Afyon Kocatepe Üniversitesi Sosyal Bilimler Dergisi, 2021)
The aim of this study is to examine students' views to the learning environment designed based on collaborative problem based learning method. To this end, the Object Oriented Programming I-II courses in the curriculum of computer programming were designed with collaborative problem solving method and students' views about this learning environment were examined. The holistic single case study design which was a type of qualitative research methods was employed in the study. The participants were 33 students taking the courses Object Oriented Programming I-II. Students worked in groups and developed software as a solution to ill structured problems which were given at the beginning of the course. At the end of the course, focus group interviews were conducted with a semi-structured interview form which was prepared by the researcher to examine students' views about the learning environment designed based on collaborative problem based learning method. As a result of focus group interview, 4 themes as positive aspects of the learning environment, challenges encountered in the learning environment, benefits of the learning environment, and skills acquired as a consequence of the learning environment were found. Some implications were presented according to the results.